Potent inhibition of TCP transcription factors by miR319 ensures proper root growth in Arabidopsis - Baulies, Julia Lidia (2022)
The evolutionarily conserved microRNA miR319 regulates genes encoding TCP transcription factors in angiosperms. The miR319-TCP module controls cell proliferation and differentiation in leaves and other aerial organs. The current model sustains that miR319 quantitatively tunes TCP activity during leaf growth and development, ultimately affecting its size. In this work we studied how this module participates in Arabidopsis root development. We found that misregulation of TCP activity through impairment of miR319 binding decreased root meristem size and root length. Cellular and molecular analyses revealed that high TCP activity affects cell number and cyclin expression but not mature cell length, indicating that, in roots, unchecking the expression of miR319-regulated TCPs significantly affects cell proliferation. Conversely, tcp multiple mutants showed no obvious effect on root growth, but strong defects in leaf morphogenesis. Therefore, in contrast to the quantitative regulation of the TCPs by miR319 in leaves, our data suggest that miR319 clears TCP transcripts from root cells. Hence, we provide new insights into the functions of the miR319-TCP regulatory system in Arabidopsis development, highlighting a different modus operandi for its action mechanism in roots and shoots.